2020
DOI: 10.3390/antiox9020172
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nano-Epigallocatechin-Gallate on Oxidative Stress and Matrix Metalloproteinases in Experimental Diabetes Mellitus

Abstract: Background: The antioxidant properties of epigallocatechin-gallate (EGCG), a green tea compound, have been already studied in various diseases. Improving the bioavailability of EGCG by nanoformulation may contribute to a more effective treatment of diabetes mellitus (DM) metabolic consequences and vascular complications. The aim of this study was to test the comparative effect of liposomal EGCG with EGCG solution in experimental DM induced by streptozotocin (STZ) in rats. Method: 28 Wistar-Bratislava rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 87 publications
0
24
0
Order By: Relevance
“…Indeed, many reports suggest that ROS are key mediators of BBB breakdown, implicating antioxidants as potential neuroprotectants against BBB-associated brain damage. ROS have also been suggested to provide a common trigger for many downstream pathways that directly mediate BBB dysfunction, such as TJ modification, and MMP activation [ 41 , 42 ]. In BBB endothelial cells, it has been shown that ROS causes DNA damage by induction of cell death, membrane lipid peroxidation, and increased permeability [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many reports suggest that ROS are key mediators of BBB breakdown, implicating antioxidants as potential neuroprotectants against BBB-associated brain damage. ROS have also been suggested to provide a common trigger for many downstream pathways that directly mediate BBB dysfunction, such as TJ modification, and MMP activation [ 41 , 42 ]. In BBB endothelial cells, it has been shown that ROS causes DNA damage by induction of cell death, membrane lipid peroxidation, and increased permeability [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in this study liposomes were used as nanocarriers, owing to its enhanced stability, bioavailability, and shelf life for sensitive ingredients as they are assembled from phospholipid bilayers similar to cell membranes and their biphasic character making them suitable for being carriers for both hydrophilic (in the central aqueous compartment) and hydrophobic (in lipid bilayers) compound. 26,27 Tuftsin a tetrapeptide (Thr-Lys-Pro-Arg) stimulates immunomodulatory effects by binding specifically to macrophages, monocytes, and polymorphonuclear leukocytes (PMN). 28 Many studies have reported the anti-tumor efficacy of tuftsin in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, Bulboaca, et al showed that i.p. administration of EGCG or liposomal EGCG improved the oxidative stress parameters such as malondialdehyde levels and nitric oxide (NO) synthesis as well as those of anti-oxidant status as evaluated by total anti-oxidant capacity and levels of thiols and catalase in plasma of rats treated with streptozotocin [ 46 ].…”
Section: Anti-cancer Effects Of Green Teamentioning
confidence: 99%